Status of Vitamin D Deficiency among the Patients in a Tertiary Care Hospital - Sinha, Amar Kumar; Shah, Tirtha Narayan; Rai, Ujwal (Medical Journal of Eastern Nepal, 2022)
Background: It has been observed that one billion people in the world have vitamin D deficiency as a public health problem. This study aims to find out the status of vitamin D in the gender of male, females, and different age groups <15 to >62 years of age. Methods: This was a retrospective study carried out at B&C Medical College Teaching Hospital and Research Centre, Jhapa from 1st January to December 31st, 2021. Vitamin D3 levels were tested with Chemiluminescence Immuno Assay (CLIA) technique. The status of vitamin D was defined as deficient if vitamin D3 level was less than 20ng/ml. We focused to find out the pattern of increased or decreased serum vitamin D level as its deficiency and surplus have an adverse effect on our health. Ethical approval was obtained from the Institutional Review Committee of B&C Medical College Teaching hospital and research Centre (Ref-0012022). Results: A total of 7,402 healthy individuals (<15->62 years of age) females 4914 (66.4%) and males 2288 (33.6%). Vitamin D deficiency was observed high in females than males. It was also observed that in the age group 15-30 years vitamin D deficiency was 52.8% which was highest among the age group and sufficiency only 18.4% were in this group. Conclusions: This study shows vitamin D deficiency was higher in females than males. If the deficiency can be deducted early, prompt management can be carried out and thus complications can be prevented.